ISOLASI OLEORESIN DARI KULIT KAYU MANIS DENGAN PROSES PERKOLASI - Jacob Ando (Jurnal Penelitian Hasil Hutan, 1987)
The result of oleoresin from Cassia vera bark by percolation process is presented in this report. The analyses comprise of the determination of oleoresin yield, essential oil and cinnamic aldehyde. The determination based on oven dry weight revealed that oleoresin yield vary from  6.27- 7.48 percent; essential oil content from 8.10-9.92 percent and cinnamic aldehyde content from 39.53-41.59 percent. The optimum yield of oleoresin was produced at temperature of 25°C and with two hours time of percolation process. Temperature and time of percolation process indicated a non significant effect to the cinnamic aldehyde yield.